Outcome of neonates requiring mechanical ventilation in a tertiary hospital - Regmi, Shanti; Pathak, Santosh; Awasti, Pusp Raj; Bhattarai, Subhash; Poudel, Rajan (Journal of Chitwan Medical College, 2018)
Mechanical ventilation is a key therapeutic modality in treatment of sick neonates. Our hospital based retrospective study conducted at Chitwan Medical College (CMC), Nepal over the duration of 2 years, from February 2015 to January 2017, with aims to study the clinical profile, indications, complications and outcome in terms of survival in mechanically ventilated neonates. Total of 119 mechanically ventilated neonates were included in the study. Along with admission and discharge register record, all the patient’s record files were retrieved from the medical record section, necessary details were entered in a predesigned proforma and statistical analysis was done using IBM SPSS 20 software. Out of 1306 total NICU admission, total 130 were mechanically ventilated, among them only 119 (9.1%) were included in the study. Majority (71.4%) were male. More than half were Preterm (51.3%) and outborn (58%). Most common indication of mechanical ventilation was sepsis followed by Birth asphyxia (BA), respiratory distress syndrome/hyaline membrane disease (RDS/HMD) and Meconium Aspiration Syndrome (MAS). Overall survival was 45(37.8%). Among the indications during the study period, the best survival observed was in birth asphyxia. Shock and Disseminated intravascular coagulation (DIC) were the two most common complications encountered during the course of ventilation. Increasing birth weight, higher gestational age and Downes Score at intubation of 6 or < 6 was associated with a better outcome. Shock, multi organ dysfunctions (MODS), and ventilator associated pneumonia (VAP) were the statistically proven individual predictors of outcome.